Hepatic damage caused by long-term high cholesterol intake induces a dysfunctional restorative macrophage population in experimental NASH - Maretti-Mira, Ana C.; Salomon, Matthew P.; Hsu, Angela M.; Kanel, Gary C.; Golden-Mason, Lucy (Frontiers in Immunology, 2022)
Excessive dietary cholesterol is preferentially stored in the liver, favoring the development of nonalcoholic steatohepatitis (NASH), characterized by progressive hepatic inflammation and fibrosis. Emerging evidence indicates a critical contribution of hepatic macrophages to NASH severity. However, the impact of cholesterol on these cells in the setting of NASH remains elusive. Here, we demonstrate that the dietary cholesterol content directly affects hepatic macrophage global gene expression. Our findings suggest that the modifications triggered by prolonged high cholesterol intake induce a long-lasting macrophage-associated hepatic damage and support the expansion of a dysfunctional pro-fibrotic restorative macrophage population even after cholesterol reduction. The present work expands the understanding of the modulatory effects of cholesterol on innate immune cells and may help identify novel therapeutic targets for NASH intervention.